The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.32607/actanaturae.11479
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antiviral Potential of Modified Heterocyclic Base and 5’-Norcarbocyclic Nucleoside Analogs Against SARS-CoV-2

Abstract: The pandemic caused by the novel betacoronavirus SARS-CoV-2 has already claimed more than 3.5 million lives. Despite the development and use of anti-COVID-19 vaccines, the disease remains a major public health challenge throughout the world. Large-scale screening of the drugs already approved for the treatment of other viral, bacterial, and parasitic infections, as well as autoimmune, oncological, and other diseases is currently underway as part of their repurposing for development of effective therapeutic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Initially designed as molecular probes for studying RNA/DNA-recognizing enzymes, fleximers have shown significant promise in antiviral research, including the development of coronavirus inhibitors [ 27 ]. Among the available fleximers, we selected the ATP mimetic Flex-nt10 (analog of 8-aza-7-deazaadenosine 5'-triphosphate), the adenosine mimetics Flex-ns10 (8-aza-7-deazaadenosine analog) and Flex-ns12 (8-aza-3,7-dideazaadenosine analog), and the deoxyadenosine mimetic Flex-dns12 [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Initially designed as molecular probes for studying RNA/DNA-recognizing enzymes, fleximers have shown significant promise in antiviral research, including the development of coronavirus inhibitors [ 27 ]. Among the available fleximers, we selected the ATP mimetic Flex-nt10 (analog of 8-aza-7-deazaadenosine 5'-triphosphate), the adenosine mimetics Flex-ns10 (8-aza-7-deazaadenosine analog) and Flex-ns12 (8-aza-3,7-dideazaadenosine analog), and the deoxyadenosine mimetic Flex-dns12 [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to purine nucleoside derivatives, we considered a well-known cytidine analog NHC (β-D-N 4 -hydroxycytidine, Figure 4 a) [ 30 ] and several recently reported pyrimidine derivatives ( Figure 4 c,d) that inhibited SARS-CoV-2 in vitro. These derivatives included 5′-norcarbocyclic (NorC) analogs of 3H-pirrolo[2,3-d]-pyrimidine-2-one (NorC-24p) and 3H-furano[2,3-d]-pyrimidine-2-one (NorC-24f) nucleosides with a hydrophobic 4-pentylphenyl substituent ( Figure 4 c) [ 29 ] and perylene-harboring uridine analogs Peryl-8 and Peryl-5 (neutral and positively charged derivatives, respectively, Figure 4 d) [ 31 ]. To verify the importance of charged and hydrophobic fragments, we also tested the non-nucleoside neutral perylene derivatives Peryl-2a and Peryl-2b, their positively charged analogs Peryl-3a and Peryl-3b, and an additional positively charged compound with in vivo-confirmed antiviral activity Peryl-10 ( Figure 4 d) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the nitrogenous base retains the necessary hydrogen bonds and aromatic properties that are required for recognition, while gaining the flexibility to adapt to the enzyme binding site and potential mutations. It has been shown that such compounds are able to inhibit the replication of HCoV-NL63 and MERS-CoV coronaviruses in cell culture [ 11 , 12 ]. The idea of fleximer compounds was developed further in the form of the synthesis of “reverse” fleximers ( Fig.…”
Section: Resultsmentioning
confidence: 99%